DETERMINATION OF RECOMMENDED LOCATIONS OF TIDE GAUGE FOR TSUNAMI EARLY WARNING BASED ON NUMERICAL MODEL (CASE STUDY: EASTERN INDONESIA) - Fadhilah, Tiara
Indonesia is the most earthquake and tsunami-prone region in the world (BMKG, 2019), which has caused many losses and took of 54,100 people (Latief et al., 2000). In the tsunami disaster mitigation phase, Indonesia launched the Indonesia Tsunami Early Warning System (InaTEWS) program by operating 160 tide gauge that can record changes in sea level. However, the tide gauge considered to be still lacking to record tsunami signals in real-time, so that the addition of tide gauge installation is needed. To recommend the new location of the tide gauge, tsunami simulations were conducted throughout eastern Indonesia using Cornell Multi-grid Tsunami Model (COMCOT) with non-linear Shallow Water Equation (NSWE). Bathymetry and topographic data are obtained from the Batimetri Nasional (BATNAS), and tide gauge distribution data is obtained from the Badan Informasi Geospasial (BIG). The source of the earthquake fault was obtained from Global Centroid-Moment-Tensor Catalog (CMT), the International Seismological Center (ISC), Pusat Studi Gempa Nasional (PUSGEN), and previous studies. The simulation results showed from 87 tide gauge evaluation selected 23 recommended tide gauge that can record the fastest first arrival time is 0 minutes.